Field‐Driven Reversal Models in Artificial Spin Ice: Field‐Driven Reversal Models in Artificial Spin Ice (Adv. Theory Simul. 7/2021). Issue 7 (14th July 2021) - Paterson, Gary W.; Macauley, Gavin M.; Macêdo, Rair
Abstract : In article number 2100109, Gary W. Paterson, Gavin M. Macauley, and Rair Macêdo evaluate models for interactions between nanoscale ferromagnetic islands in artificial spin ice under field‐driven processes. The work shows how the emergent properties of a continuum of island arrangements from 'square' to 'pinwheel' are influenced in different ways by the non‐Ising nature of the islands, and how the efficient modeling of these and similar systems may be improved.